Fundamental of Entrepreneurship ENT300 Hermosa Spa / Wilbur Anak Augustine... [et.al] - Augustine, Wilbur; John Tabok, Natasha; Hipni, Fadzrul; Jineus, Michael Hillary; Johnny, Eliza Yvonne (2015)
After doing extensive research on the business opportunity available in Matang Jaya area, our group decided to specify our business. Our group has come up with the business plan of partnership, known as HERMOSA SPA. The business has been decided on the form of five partnerships. Each partner has contributes certain amount of capital as agreed in our agreement. We will open our spa at The Hub@Matang Jaya and hopefully will open by 1st August 2016.